Investigation of a Microcystis aeruginosa cyanobacterial freshwater harmful algal bloom associated with acute microcystin toxicosis in a dog - van der Merwe, Deon; Sebbag, Lionel; Nietfeld, Jerome C.; Aubel, Mark T.; Foss, Amanda; Carney, Edward (My University, 2012)
Microcystin poisoning was diagnosed in a dog exposed to a Microcystis aeruginosa dominated freshwater harmful algal bloom at Milford Lake, Kansas, which occurred during the summer of 2011. Lake water microcystin concentrations were determined at intervals during the summer, using competitive enzyme-linked immunosorbent assays, and indicated extremely high, localized microcystin concentrations of up to 126,000 ng/ml. Multiple extraction and analysis techniques were utilized in the determination of free and total microcystins in vomitus and liver samples from the poisoned dog. Vomitus and liver contained microcystins, as determined by enzyme-linked immunosorbent assays, and the presence of microcystin LR was confirmed in vomitus and liver samples using liquid chromatography coupled with tandem mass spectrometry. Major toxic effects in a dog presented for treatment on the day following exposure included fulminant liver failure and coagulopathy. The patient deteriorated rapidly in spite of aggressive treatment, and was euthanized. Postmortem lesions included diffuse, acute, massive hepatic necrosis and hemorrhage, and acute necrosis of the renal tubular epithelium. A diagnosis of microcystin poisoning was based on the demonstration of M. aeruginosa and microcystin-LR in the lake water, as well as in vomitus produced early in the course of the poisoning, the presence of microcystin-LR in liver tissue, and on a typical clinical course.
Keywords: Microcystis aeruginosa; Microcystin; Liver failure; Renal failure